Analisis Aktivitas Antioksidan Pada Fraksi Aktif Kacang Lebui Lombok (Cajanus cajan) - Febriani, Yuyun; Habibatusshalihah, Habibatusshalihah (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Cajanus cajan or known as lebui is one of the local plants of Lombok which is used as a side dish and in some places empirically used as a treatment. This study aims to identify and analyze the antioxidant activity of the active fraction of lebui beans with various solvent variations. The design of post-test was used this study. The extract used was 96% ethanol extract with liquid-liquid fractionation method in various solvents such as methanol, n-hexane, and ethyl acetate. The results obtained were tested by thin layer chromatography with a standard comparison of vitamin C (ascorbic acid) in the eluent composition of ethyl acetate: methanol: formic acid (8:2:0,5). The antioxidant activity test used two tests, namely qualitative testing by spraying DPPH on the TLC plate and quantitative testing using UV-Vis’s spectrophotometer. The TLC test results obtained that the Rf value of lebui bean extract was 0.8, the Rf value for fraction I (n-hexane) was 0.8, the Rf value for fraction II (ethyl acetate) was 0.8, the Rf value for fraction III (methanol) was 0.2 and the standard Rf value for vitamin C was 0.8. The results of the qualitative test showed that fraction I and fraction II contained antioxidants. Further quantitative testing showed that the IC50 value of fraction I (N-Hexane), fraction II (Ethyl Acetate, and standard respectively were 148 ppm, 88.4 ppm, and 48 ppm. Based on this, it can be concluded that lebui beans have antioxidant activity in the category of strong antioxidant activity and more fracted on more polar solvent